Avaliação da equivalência farmacêutica da Carbamazepina e Diazepam comercializados no Programa de farmácia popular do Brasil - Wong, Deysi Viviana Tenazoa (2009)
Two drugs are considered pharmaceutically equivalent when both contain the same drug (base, salt or ester of the same active ingredient), at the same dosage and pharmaceutical form determined in vitro. In Brazil, the allopathic drugs are classified into three cathegories when registered in the Brazilian health surveillance agency (Agência Nacional de Vigilância Sanitária): new, similar or generic drugs. This work aimed to determine the pharmaceutical equivalence of Carbamazepine 200 mg (CBZ) and Diazepam 10 mg (DZP) marketed in the Brazil Popular Pharmacy program, discussing the importance of drugs for public health. Carbamazepine SQR and Diazepam SQR were used as reference drugs with 99.6 and 99.9% declared content, respectively. Physicochemical studies, such as mean weight, disintegration, hardness, friability, content, content uniformity and dissolution profile were performed in accordance to Brazilian Pharmacopeia 4th edition. The results indicated a lower hardness of DZP Popular Pharmacy tablets. Despite the dissolution profile of CBZ, the ANOVA test presented significant statistical difference (p<0.05) between Popular Pharmacy tablets and generic or reference drugs in all the time point evaluated. The dissolution profile of Popular Pharmacy and reference tablets were compared through the f1 (difference) and f2 (similarity) factors. Values of 46.29 and 35.00 respectively were found suggesting a difference on the profiles evaluated. The DZP tablets, despite the sample, showed a dissolution fraction higher than 85% in 15 minutes. f1 and f2 were not possible to be calculated in these cases. The variance analysis evidenced, for all the samples, statistical difference (p< 0.05) in the first 75 minutes evaluated, what might not have pharmaceutical importance. The other physicochemical parameters were in accordance with Brazilian Pharmacopeia for all the CBZ and DZP samples. Therefore, the CBZ tables cannot be considered pharmaceutically equivalents to the reference ones.